The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/econometrics1020157
|View full text |Cite
|
Sign up to set email alerts
|

Parametric and Nonparametric Frequentist Model Selection and Model Averaging

Abstract: This paper presents recent developments in model selection and model averaging for parametric and nonparametric models. While there is extensive literature on model selection under parametric settings, we present recently developed results in the context of nonparametric models. In applications, estimation and inference are often conducted under the selected model without considering the uncertainty from the selection process. This often leads to inefficiency in results and misleading confidence intervals. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 99 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Frequentist Model Averaging (FMA). FMA [61,63,[244][245][246][247] is a relatively new multimodeling approach for dealing with model uncertainty that addresses several issues associated with Bayesian methods [58,183,226,230,236,242,243]. In particular, FMA doesn't require prior distributions be specified for either predictors or models and permits flexibility in weight choice for FMA estimators [246].…”
Section: Multimodel (Mm) Search and Averaging Methodsmentioning
confidence: 99%
“…Frequentist Model Averaging (FMA). FMA [61,63,[244][245][246][247] is a relatively new multimodeling approach for dealing with model uncertainty that addresses several issues associated with Bayesian methods [58,183,226,230,236,242,243]. In particular, FMA doesn't require prior distributions be specified for either predictors or models and permits flexibility in weight choice for FMA estimators [246].…”
Section: Multimodel (Mm) Search and Averaging Methodsmentioning
confidence: 99%
“…3 Following Ullah and Wang (2013) and Hurvich et al (1998) we also calculated the Akaike information criterion (AIC), which again proved that Model A performs best.…”
Section: Model Comparisonmentioning
confidence: 96%
“…This literature on forecast combinations (discussed here more in detail in Subsection 4.3) has become quite voluminous, see e.g. Granger (1989) and Stock and Watson (2006) for reviews, while useful surveys of FMA can be found in Burnham and Anderson (2002), Wang et al (2009), Ullah and Wang (2013) and Dormann et al (2018).…”
Section: Frequentist Model Averagingmentioning
confidence: 99%